Pengaruh Limbah Karbit / Calcium Carbit Sebagai Bahan Substitusi Semen Pada Beton - Liberty Juniasy Somalinggi; Frans Phengkarsa; Lisa Febriani (Paulus Civil Engineering Journal, 2020)
This study utilizes carbide waste as a partial substitute for cement in the manufacture of beons which aims to determine the optimum value of adding carbide waste which functions as a partial cement substitute for compressive strength, split tensile strength, and modulus of elasticity of concrete. Variations of carbide waste are 0%, 4%, 6%, and 8%. The sample used was a cylinder with a diameter of 15 cm and a height of 30 cm as many as 72 samples. The compressive strength test was carried out at the age of 3 days, 7 days, 14 days, 21 days, and 28 days, and the split tensile strength and modulus of elasticity were tested at the age of 28 days. The results showed that the concrete with 4% carbide waste obtained the optimum test results for all tests.